Pengaruh Inflasi, Suku Bunga dan Kebijakan Dividen Terhadap Harga Saham dengan Profitabilitas sebagai Variabel Moderasi pada Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Nurul Faizatil Karimah; Betra Agus Petra; Yosi Puspita Sari (GLOBAL SCIENTS PUBLISHER, 2026)
The movement of stock prices in the banking sector within the Indonesian capital market demonstrates high sensitivity to changes in macroeconomic conditions and corporate policies. This study examines the effect of inflation, interest rates, and dividend policy on stock prices, with profitability as a moderating variable in banking companies listed on the Indonesia Stock Exchange during 2020–2024. Secondary data were obtained from annual financial reports and official capital market publications. The sample consists of 15 banking companies selected through purposive sampling. Data were analyzed using descriptive statistics, panel data regression, and moderated regression analysis. The results indicate that inflation, interest rates, and dividend policy do not have a significant partial effect on stock prices. However, profitability moderates the influence of inflation and dividend policy on stock prices, while it does not moderate the relationship between interest rates and stock prices. These findings suggest that internal financial performance plays a more decisive role than macroeconomic variables in shaping banking stock price movements.